Use of Oral Tramadol to Prevent Post-anaesthetic Shivering in Patients Undergoing Surgery under Spinal Anaesthesia - Acharya, Sulav; Dangol, Sanam (Nepal Medical College Journal, 2023)
Shivering is a common and distressing problem after spinal anaesthesia which occurs due to heat loss and core to peripheral redistribution of body heat, resulting in reduction of core body temperature. Post anaesthetic shivering has deleterious metabolic and cardiovascular effect which should ideally be prevented by pharmacological methods that are economically and practically feasible in all settings compared to many physical methods. Therefore, this study was conducted using a centrally acting analgesic, oral Tramadol hydrochloride prophylactically for the prevention of perianaesthetic shivering after spinal anaesthesia. This prospective observational study was carried out in 106 patients of ASA I or II, aged 15 to 70 yrs of age undergoing lower limb or lower abdominal surgery under spinal anaesthesia. Postanaesthetic shivering was evaluated during the surgery. Shivering was observed in 11 (10.4%) patients and among them 2 (1.9%) patients had grade 1, 6 (5.7%) patients had grade 2, 2 (1.9%) patients had grade 3 and 1 (0.9%) patients had grade 4 type of shivering. Sedation was observed in 19 (17.9%) patients. The result of this study concluded that oral tramadol is very safe and superior to various drugs studied till date and can be used prophylactically as a part of premedication for the prevention of postanaesthetic shivering in patients undergoing surgery under spinal anaesthesia.